Analisis Tentang Pertumbuhan Ekonomi Indonesia Periode Tahun 2009 – 2018 - Bonaraja Purba (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2020)
This study aims to determine the impact of Foreign Direct Investment (FDI), Export and Foreign Debt on Economic Growth of Indonesia for Period of Year 2009 - 2018. The type of this research used is explanatory research with quantitative approach. The location of this study was conducted at the World Bank through the website www.worldbank.org. The population in this study is the whole time series data from FDI, exports, foreign debt and economic growth of Indonesia. The sampling technique is by collecting time series data for 10 years that 2009 - 2018 so that there are 40 samples. Data analysis used is multiple linear regression analysis. The results of data analysis in this study indicate that the variables consisting of FDI, exports, foreign debt simultaneously have significant effect to the economic growth of Indonesia. Partially FDI has significant effect on economic growth of Indonesia. Exports has significant effect on economic growth of Indonesia. Foreign debt has significant effect on economic growth of Indonesia.